Primary cardiac lymphoma: a clinicopathological study of 121 cases - Zhuang, Shuhui; Chang, Liudi; Feng, Xiaoxi; Hu, Weiwen; Yang, Zhaobo; Zhang, Yuanyuan (Frontiers in Oncology, 2025)
BackgroundPrimary cardiac lymphoma (PCL) is an exceedingly uncommon type of lymphoma that primarily affects the heart and/or pericardium, or manifests through cardiac symptoms due to myocardial infiltration. The infrequency of PCL, coupled with its non-specific clinical presentations, often complicates early diagnosis. This study aims to fill the existing gap in clinical knowledge regarding PCL by detailing a case of PCL and examining its clinical features, auxiliary examinations, treatment approaches, and prognostic outcomes, thereby facilitating early detection and enhancing patient care.MethodsA thorough search of the PubMed and Chinese National Knowledge Infrastructure (CNKI) database was performed using keywords “heart” and “lymphoma” or “primary cardiac lymphoma”. This search encompassed publications from January 1, 2014, to November 1, 2024.ResultsThe review included 121 cases. These cases usually present with atypical symptoms, mainly circulatory and respiratory, including chest tightness, dyspnea, and edema, along with occasional neurological and gastrointestinal symptoms. Echocardiography served as the primary diagnostic method in 92.6% of cases, while a definitive diagnosis was achieved through pathological examination in all cases (100%). Treatment strategies predominantly included surgical intervention (44.6%) and chemotherapy (76.0%). Although surgery did not have a significant effect on survival rates, chemotherapy proved to be critical in improving patient survival.ConclusionsPCL, which arises in the cardiac or pericardial areas, is generally associated with a poor prognosis. It is essential for clinicians to develop a greater awareness and understanding of the characteristics of PCL to enhance early diagnosis. The timely initiation of chemotherapy is vital for improving survival rates and the overall quality of life for patients with PCL.